2011
DOI: 10.1016/j.jacc.2011.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Birth Prevalence of Congenital Heart Disease Worldwide

Abstract: Congenital heart disease (CHD) accounts for nearly one-third of all major congenital anomalies. CHD birth prevalence worldwide and over time is suggested to vary; however, a complete overview is missing. This systematic review included 114 papers, comprising a total study population of 24,091,867 live births with CHD identified in 164,396 individuals. Birth prevalence of total CHD and the 8 most common subtypes were pooled in 5-year time periods since 1930 and in continent and income groups since 1970 using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

50
1,840
16
80

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,733 publications
(1,986 citation statements)
references
References 21 publications
50
1,840
16
80
Order By: Relevance
“…It has increased steadily since 1930. The birth prevalence since 1995 ranges between 1.9 and 9.3/1000 births [4], [5], [8]. The current lower prevalence in Africa is similar to that in the West in the early 1930s (0.6/1000 births) and is probably related to an under diagnosis.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…It has increased steadily since 1930. The birth prevalence since 1995 ranges between 1.9 and 9.3/1000 births [4], [5], [8]. The current lower prevalence in Africa is similar to that in the West in the early 1930s (0.6/1000 births) and is probably related to an under diagnosis.…”
Section: Introductionmentioning
confidence: 92%
“…Congenital heart disease (CHD) and early acquired heart disease (EAHD) are of special importance in adolescents as they may impact their subsequent health as they age [2], [3]. Many studies which investigated the prevalence of CHD in fetal and newborn populations found fewer subjects than in population studies of older children and adolescents [4], [5]. Echocardiographic screening revealed a prevalence rate of approximately 3.5% for cardiac lesion in older children [6], [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence has been reported to be around 1/33 000 live births, accounting for ≈0.05% of congenital heart malformations 2. Although a familial recurrence of heart defects in subjects with ccTGA has been reported,3 the etiology of this malformation is not currently known 1, 4…”
Section: Introductionmentioning
confidence: 99%
“…Congenital heart disease (CHD) is the most common category of birth defect, with an incidence rate between 0.3% and 0.8% 1, 2. Critical CHD (CCHD)—defined as requiring neonatal intervention—is reported to have an incidence rate of 0.17% 3.…”
Section: Introductionmentioning
confidence: 99%